Perbandingan Profitabilitas Sebelum Dan Sesudah Pandemi Covid-19 Pada Perusahaan E-Commerce (Studi Kasus pada Sektor Teknologi di BEI) Tahun 2016 – 2023 - Siti Rahmah; Diah Yudhawati; Angga Prasetia (CV. ITTC INDONESIA, 2024)
The COVID-19 pandemic has had a major impact on various economic sectors around the world, including the technology and e-commerce sectors in Indonesia. This study aims to analyze the differences in profitability of e-commerce companies listed in the technology sector on the Indonesia Stock Exchange (IDX) before and after the COVID-19 pandemic, with a study period of 2016 - 2023. The population in this study is e-commerce companies in the technology sector. The sampling technique used purposive sampling which obtained 11 e-commerce companies in the technology sector on the Indonesia Stock Exchange. By using a different test (Wilcoxon Signed Rank Test), the results of the Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) variables did not have a significant difference in profitability in e-commerce companies in the technology sector before and after the COVID-19 pandemic.